Looking at the high ability/giftedness through the lens of curriculum studies - Soraia Napoleão Freitas; Claus Dieter Stobäus (Universidade Federal de Santa Maria (UFSM), 2011)
From diving in the educational field, either in teaching or research in Special Education, this article postulates bring visibility to a curricular discussion strongly marked by the educational practice of learners with high ability/giftedness and having the "lighthouse flag" the inclusion policy school principles, not just theorizing about the elements of the theme. Curriculum is understood as a territory of knowledge and power, so the manufacturing process of the curriculum in the wake of the inclusive hillside - a journey which aims to solidify egalitarian social link - can put up as an potentiating agent of different actions for the education of students with high ability/giftedness, protecting them from moments of discrimination, segregation and personal, family, school and social exclusion. Therefore, this article takes up an invitation to educators to look at the prerogatives of education that hosts students with high ability/giftedness with the lens of curriculum studies.